Features of the Area under the Receiver Operating Characteristic (ROC) Curve. A Good Practice. (March 2016) - Lora, David; Contador, Israel; Pérez-Regadera, José F.; de la Cámara, Agustín Gómez
The area under the receiver operating characteristic (ROC) curve is a measure of discrimination ability used in diagnostic and prognostic research. The ROC plot is usually represented without additional information about decision thresholds used to generate the graph. In our article, we show that adding at least one or more informative cutoff points on the ROC graph facilitates the characterization of the test and the evaluation of the discriminatory capacities, which can result in more informed medical decisions. We use therocreg androcregplot commands.